Internal and External Context Specificity of Leadership in M&A Integration - Hauser, Bettina (Springer, 2015)
Bettina Hauser develops a research model, which encompasses entrepreneurial leadership as a major success factor during post-merger integration. Additionally, contextual variables, namely cultural distance and the organizational variable, relative size, are tested for their moderating effect on the influence of entrepreneurial leadership on M&A performance. The author clarifies the question of how entrepreneurial leadership can help to enhance M&A performance. Based on 114 transactions with acquirers of German-speaking companies, she proves that entrepreneurial leadership has a positive effect on post-acquisition performance and helps to overcome problems related to cultural differences.